Diskusi Refleksi Kasus (DRK) Efektif Meningkatkan Kemampuan Perawat dalam Melakukan Dokumentasi Keperawatan Sesuai Standar 3s (SDKI, SLKI, SIKI) - Sudaryati Sudaryati; Tuti Afriani; Rr. Tutik Hariyati; Rita Herawati; Yunita Yunita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of Case Reflection Discussion (DRK) on improving nurses' ability to carry out nursing documentation according to 3S standards (IDHS, SIKI, SLKI) Hospital X Jakarta. The method used in this research is using a pilot project starting from problem identification, problem analysis and problem priority setting, preparation of a Plan of Action (POA), implementation, and evaluation. The results obtained are that there is an increase in the ability of nurses in preparing nursing diagnoses according to the IDHS standards by 40% after the Case Reflection Discussion (DRK) and an increase in the knowledge of nurses in preparing interventions and outcomes according to the SIKI and SLKI standards by 24% after carrying out the Case Reflection Discussion ( DRK). In conclusion, Case Reflection Discussion (DRK) is very efficient in improving the ability of nurses to carry out nursing documentation according to 3S standards (IDHS, SLKI, SIKI). Keywords: Case Reflection Discussion, Nursing Documentation, IDHS, SIKI, SLKI